New toxicity testing of PQ grass allergy immunotherapy to support product development. Issue 10 (23rd June 2019) - Baldrick, Paul; Hutchings, James W.; Heath, Matthew D.; Skinner, Murray A.; Martin, Tom; Gray, Chris
Abstract: PQ Grass represents an allergen‐specific immunotherapy for pre‐seasonal treatment of patients with seasonal allergic rhinitis (or rhinoconjunctivitis) with or without mild‐ to‐ moderate bronchial asthma. It consists of a native pollen extract for 13 grass species, chemically modified with glutaraldehyde, and adsorbed tol ‐tyrosine in a microcrystalline form with addition of the adjuvant Monophosphoryl Lipid A (MPL ® ). Previous non‐clinical safety testing, including rat repeat dose toxicity in adult and juvenile animals, rat reproductive toxicity and rabbit local tolerance studies showed no safety findings of concern. A new Good Laboratory Practice compliant rat subcutaneous repeat dose toxicity study to evaluate a higher clinical dose and modified posology (once every 2 weeks for 13 weeks) showed no signs of toxicity. As seen in previous studies, relatively minor, immunostimulatory effects were seen such as reversible increased white cell count (notably neutrophils), increased globulin level (resulting in decreased A/G ratio) and increased fibrinogen as well as minor dose site reaction in the form of inflammatory cell infiltrate. These findings are likely due to the immunostimulatory nature of MPL and/or the presence ofl ‐tyrosine within the adjuvanted vaccine. This new toxicity study with PQ Grass therefore supports longer posology with higher dose levels. Abstract : PQ Grass represents an allergen‐specific immunotherapy for pre‐seasonal treatment of patients with seasonal allergic rhinitis. Previous non‐clinical safety testing showed no safety findings of concern. A new rat repeat dose study with PQ Grass to evaluate a higher clinical dose and modified posology was performed and showed no signs of toxicity.